Beyond the Mutual Constitution of States and Markets: On the Governance of Alienation. Issue 3 (4th May 2021) - Copley, Jack; Moraitis, Alexis
ABSTRACT: International Political Economy (IPE) textbooks tend to present the concept of a clear state-market dichotomy as the disciplinary mainstream. Yet we argue that a critical consensus has emerged around the mutual constitution of states and markets. Underpinning this is the Polanyian thesis that economic activities are always politically embedded. However, we claim that this notion of state-market mutual constitution is inadequate to grasp the peculiarities of the capitalist political economy. While capitalist market relations are underpinned by states, they take on an autonomous, dominating logic that limits states' agency. Concretely, by reproducing international monetary relations, states accidentally contribute to the establishment of world labour productivity averages that force them to boost national competitiveness in order to keep pace with world market standards. In place of the notion of mutual constitution, then, we offer Marx's concept of alienation as a theory of a form of social relations that have escaped the control of the institutions that produce them. The challenge of state governance – reflected in the canon of liberal thought – is to reconcile the impersonal imperatives of world market relations with the creation of a legitimate national political project, which we term the politics of governing alienation .